Israel : 2007 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Israel. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The Israeli economy is performing exceptionally well, but still high public indebtedness calls for the continuation of strong economic policies. Monetary policy has successfully stabilized inflation expectations, but policy and communication challenges remain. The recent positive fiscal performance needs to be carried forward to improve international credibility. The government's intention to stick with a rules-based approach to fiscal policy, solidly anchored in longer-term objectives, is commended. Enhanced fiscal transparency and governance are essential to improve the quality of policymaking.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet